Amyloid burden and sleep blood pressure in amnestic mild cognitive impairment. (1st December 2015) - Tarumi, Takashi; Harris, Thomas S.; Hill, Candace; German, Zohre; Riley, Jonathan; Turner, Marcel; Womack, Kyle B.; Kerwin, Diana R.; Monson, Nancy L.; Stowe, Ann M.; Mathews, Dana; Cullum, C. Munro; et al.
Abstract : Objective: To determine whether cortical β-amyloid (Aβ) deposition is associated with circadian blood pressure (BP) profiles and dynamic cerebral blood flow (CBF) regulation in patients with amnestic mild cognitive impairment (aMCI). Methods: Forty participants with aMCI were included in this study. Cortical Aβ depositions were measured by 18 F-florbetapir PET and expressed as the standardized uptake value ratio (SUVR) relative to the cerebellum. Circadian BP profiles were measured by 24-hour ambulatory monitoring during awake and sleep periods. The dipping status of sleep BP (i.e., the percent changes from the awake BP) was calculated and dichotomized into the dipper (≥10%) and nondipper (<10%) groups. Dynamic CBF regulation was assessed by a transfer function analysis between beat-to-beat changes in BP and CBF velocity measured from the middle cerebral artery during a repeated sit-stand maneuver. Results: Age was positively correlated with a greater Aβ deposition in the posterior cingulate, precuneus, and mean cortex. Accounting for the age effect, attenuated reductions in sleep systolic BP were associated with higher levels of posterior cingulate SUVR. Consistently, the nondippers exhibited a higher SUVR in the posterior cingulate than the dippers. Transfer function gain between changes in BP and CBF velocity was diminished in the nondippers, and moreover those individuals with a lower gain exhibited a higher SUVR in the posterior cingulate. Conclusions: Attenuated reductions in sleep BP are associated with a greater Aβ burden in the posterior cingulate and altered dynamic CBF regulation in patients with aMCI.